2013
DOI: 10.1038/nmat3810
|View full text |Cite
|
Sign up to set email alerts
|

Local electrostatic imaging of striped domain order in LaAlO3/SrTiO3

Abstract: The emerging field of complex oxide interfaces is generically built on one of the most celebrated substrates--strontium titanate (SrTiO3). This material hosts a range of phenomena, including ferroelasticity, incipient ferroelectricity, and most puzzlingly, contested giant piezoelectricity. Although these properties may markedly influence the oxide interfaces, especially on microscopic length scales, the lack of local probes capable of studying such buried systems has left their effects largely unexplored. Here… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
173
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(197 citation statements)
references
References 34 publications
19
173
1
3
Order By: Relevance
“…17 More recently, the presence of tetragonal domains in STO (at low temperature) was demonstrated to alter locally the conductance. 18,19 Finally, the control of the LAO surface state was shown to be an efficient lever to enhance the interfacial electron mobility. 8,20,21 In this letter, we perform a systematic study of the effect of the growth temperature (T g ) on the transport properties of the LAO/STO interface.…”
mentioning
confidence: 99%
“…17 More recently, the presence of tetragonal domains in STO (at low temperature) was demonstrated to alter locally the conductance. 18,19 Finally, the control of the LAO surface state was shown to be an efficient lever to enhance the interfacial electron mobility. 8,20,21 In this letter, we perform a systematic study of the effect of the growth temperature (T g ) on the transport properties of the LAO/STO interface.…”
mentioning
confidence: 99%
“…In terms of the original cubic directions, the twin planes are along (110) p , (101) p , and (011) p . Recent studies have shown that the low-temperature twin structure affects both the interfacial conductivity in LaAlO 3 /SrTiO 3 heterostructures [42,43] and the superconducting transition temperature in STO [44].We measured the magnetic spatial landscape in four EuS/STO-based heterostructures using a scanning superconducting quantum interference device (SQUID) susceptometer in a 4 He cryostat. Unless otherwise indicated, the data in this paper were taken on a thin film (5 nm) of (001) p -oriented EuS grown on a (001) p -oriented STO substrate, but we observed similar effects in samples with (110) p -and (111) p -oriented STO substrates and samples with 3-nm-thick EuS [45].…”
mentioning
confidence: 99%
“…We note that lattice tilting is also observed across grain boundaries in oxide systems, for example across a twin grain boundary in tetragonal SrTiO 3 [162] or PbTiO 3 [163]. In both cases the tilting can be described using a simplified version of equation (4.1), since across the domain wall a and c are exchanged and the 'ramp' angle can be defined by arctan (a/c), leading to γ = 2 arctan(c/a) − 90 • .…”
Section: Other Materials Combinationsmentioning
confidence: 70%
“…A structure like this can be measured quite easily with a technique like nXRD, which has sufficient resolution to measure the local tilt of the lattice. This technique is preferred over a [162] [163]…”
Section: Other Materials Combinationsmentioning
confidence: 99%
See 1 more Smart Citation